Talion w świetle "Noctes Atticae" Aulusa Gelliusa - Zabłocki, Jan (Prawo Kanoniczne, 1995)
Aulus Gellius presented a discussion between a philosopher and a layer in his Noctes Atticae. According to Sextus Caecilius who was the lawyer the talon had been antiquated in the days of the Law of the Twelve Tables and it was substituted by pecuniary penalties. However, the praetor’s activity affected the abandonment of fines with amounts fixed in the Twelve Tables in favour of a penalty for iniuria which was estimated by a judge. It was similar the case of membri ruptio, when an offender had decided to avoid the talon. Yet Favorinus who was the philosopher emphasized that choice o f talon belonged to a sufferer. Nevertheless, he noted its cruelty and problems with the just execution of the talon. His attitude did not surprise: he took no account of social and legal circumstances not only of the time of the Twelve Tables, but of his own days as well. Defending the humanitarianism of the Twelve Tables, the layer analized their clauses in the broad cultural and legal context. He did not allege that the talon had been humanitarian, but he tended to clarify that the penalty had to be accepted by the offender and it was executed only on himself.